The Problems of Using Gadgets on Interest in Learning to Read the Qur'an - Dian Ari Setianingsih; Ainun Nadlif (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to find out the problems of using gadgets on interest in learning to read the Qur'an in elementary school age children in Gading Krembung Village, Sidoarjo. This research is a descriptive qualitative research. In this study, the informants were the head of Gading village, parents of elementary school age children, and Ustadz/ustadzah TPQ in Gading Krembung village, Sidoarjo. The location of this research is in Gading Krembung Village, Sidoarjo. Data collection techniques in the form of interviews, observation, documentation. Data analysis and interpretation techniques use the analytical model of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the intensity of the use of gadgets has an impact on the interest in learning to read the Qur'an in elementary school age children (SD). They often use their gadgets for a long time, which is more than 2 hours per day. The use of gadgets in children with a duration of more than 2 hours per day is often used only for playing games, youtube, tiktok, and learning media. When children operate gadgets for a long enough duration, it will also make children addicted to playing gadgets and experience a decrease in their interest in learning. Furthermore, the problems experienced by elementary school age children are the lack of supervision from parents in the use of gadgets, lack of knowledge about good use of gadgets for parents and children, self factors, peer factors, and environmental factors. So that the use of gadgets affects interest and enthusiasm in learning to read the Qur'an. Seeing this fact, the use of gadgets has an effect on interest and enthusiasm in learning to read the Qur'an.